Optimalisasi Sumber Mata Air Melalui Sistem Bioponik di Dusun Sumber-Timpik - Joko Siswanto; Muhammad Fathul Anwar; Yuni Falah Utami; Putriya Alifia; Aji Candra Wibiantoro; Vinsensius Singgih (Universitas Veteran Bangun Nusantara, 2024)
Sumber-Timpik Village is one of the villages in Semarang Regency which has good springs and has the potential to be developed. However, so far not many people in the Village have used the spring water as a profitable business. The aim of this Community Service activity is to transfer or share knowledge and provide skills to partners to be able to optimize these water sources. The partners in this activity are the Pagumas fish group whose members consist of the Sumber-Timpik Village community. The service activities carried out include program outreach and pre-test; socialization of material regarding Bioponics; training in making Biofloc ponds; pond water fermentation training; Aquapony making training; seeding training; aquaponics practices; as well as control and post-test. This community service activity was declared successful with indicators of increasing participants' knowledge and skills by 54.22%, namely increasing biofloc knowledge and skills; increased aquaponics knowledge and skills; increasing the cultivation of fish and vegetable plants using Bioponics, as well as increasing knowledge regarding the effectiveness and efficiency of Bioponic systems. Keywords : springs, cultivation, biofloc, aquaponics